Perinatal mood and anxiety disorders, serious mental illness, and delivery-related health outcomes, United States, 2006–2015 - McKee, Kimberly; Admon, Lindsay K.; Winkelman, Tyler N. A.; Muzik, Maria; Hall, Stephanie; Dalton, Vanessa K.; Zivin, Kara (BMC women's health, 2020)
National estimates of perinatal mood and anxiety disorders (PMAD) and serious mental illness (SMI) among delivering women over time, as well as associated outcomes and costs, are lacking. The prevalence of perinatal mood and anxiety disorders and serious mental illness from 2006 to 2015 were estimated as well as associated risk of adverse obstetric outcomes, including severe maternal morbidity and mortality (SMMM), and delivery costs. The study was a serial, cross-sectional analysis of National Inpatient Sample data. The prevalence of PMAD and SMI was estimated among delivering women as well as obstetric outcomes, healthcare utilization, and delivery costs using adjusted weighted logistic with predictive margins and generalized linear regression models, respectively. The study included an estimated 39,025,974 delivery hospitalizations from 2006 to 2015 in the U.S. PMAD increased from 18.4 (95% CI 16.4-20.0) to 40.4 (95% CI 39.3-41.6) per 1000 deliveries. SMI also increased among delivering women over time, from 4.2 (95% CI 3.9-4.6) to 8.1 (95% CI 7.9-8.4) per 1000 deliveries. Medicaid covered 72% (95% CI 71.2-72.9) of deliveries complicated by SMI compared to 44% (95% CI 43.1-45.0) and 43.5% (95% CI 42.5-44.5) among PMAD and all other deliveries, respectively. Women with PMAD and SMI experienced higher incidence of SMMM, and increased hospital transfers, lengths of stay, and delivery-related costs compared to other deliveries (P < .001 for all). Over the past decade, the prevalence of both PMAD and SMI among delivering women increased substantially across the United States, and affected women had more adverse obstetric outcomes and delivery-related costs compared to other deliveries.